India and Pakistan: United by Covid-19 - Fatima, Syeda Sidra; Faheem, Samar (Journal of the Pakistan Medical Association, 2021)
Madam, the number of new Covid-19 cases in India peaked at 362,902 on the 27th of April, 2021.1 This is the highest single day total for the world. India sold double the oxygen in 2020-21 than the previous year, now it faces a shortage of medical oxygen as it struggles with rising cases.2 Additionally, it struggles with the vaccine drive. In an article, Kamala Thiagarajan states that the initial block was mistrust of local vaccines, even among frontline healthcare workers. Other conspiracies followed, including fear of price hikes and reports about adverse effects, as approval for its own vaccines was rushed without proper evaluation to ensure safety.3 When adverse effects were observed in AstraZeneca and Johnson & Johnson trials, they were paused to conduct a safety review. However, no such thing occurred during the Covaxin trial.4 Continuous...